2017
DOI: 10.1002/jor.23640
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of miR‐146a, miR‐149, miR‐196a2, and miR‐499 are associated with osteoporotic vertebral compression fractures in Korean postmenopausal women

Abstract: Genetic factors have been shown to be a small but significant predictor for osteoporosis and osteoporotic fracture risk. We performed a case-control association study to determine the association between miR-146a, miR-149, miR-196a2, and miR-499 polymorphisms and osteoporotic vertebral compression fracture (OVCF) susceptibility. In total, 286 unrelated postmenopausal Korean women (57 with OVCFs, 55 with non-OVCFs, and 174 healthy controls) were recruited. All subjects underwent dual energy X-ray absorptiometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The results showed that: 1) the TT genotype of miR‐149aT>C was less frequent in subjects with OVCFs, suggesting a protective effect against OVCFs; 2) the miR‐146aCG/miR‐196a2TC combined genotype was more frequent in OVCF patients, suggesting an increase in OVCF risk; and 3) combinations of miR‐146a, miR‐149, miR‐196a2, and miR‐449 showed a significant association with increased prevalence of OVCFs in postmenopausal women, especially with the miR‐146aG/miR‐149T/miR‐196a2C/miR‐449G allele combination, which was significantly associated with an increased risk of OVCF. As such, the authors concluded that the TT genotype of miR‐149aT>C may contribute to a decreased susceptibility to OVCF while the miR‐146aCG/ miR‐196a2TC combined genotype and the miR‐146aG/miR‐149T/miR‐196a2C/miR‐449G allele combination may contribute to increased susceptibility to OVCF in Korean postmenopausal women …”
Section: Mirna Polymorphisms and Human Fracturesmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that: 1) the TT genotype of miR‐149aT>C was less frequent in subjects with OVCFs, suggesting a protective effect against OVCFs; 2) the miR‐146aCG/miR‐196a2TC combined genotype was more frequent in OVCF patients, suggesting an increase in OVCF risk; and 3) combinations of miR‐146a, miR‐149, miR‐196a2, and miR‐449 showed a significant association with increased prevalence of OVCFs in postmenopausal women, especially with the miR‐146aG/miR‐149T/miR‐196a2C/miR‐449G allele combination, which was significantly associated with an increased risk of OVCF. As such, the authors concluded that the TT genotype of miR‐149aT>C may contribute to a decreased susceptibility to OVCF while the miR‐146aCG/ miR‐196a2TC combined genotype and the miR‐146aG/miR‐149T/miR‐196a2C/miR‐449G allele combination may contribute to increased susceptibility to OVCF in Korean postmenopausal women …”
Section: Mirna Polymorphisms and Human Fracturesmentioning
confidence: 99%
“…Similarly, a case–control association study was conducted to determine the link between miR‐146a, miR‐149, miR‐196a2, and miR‐499 (based on previous reports of their effects on skeletal cells) polymorphisms and osteoporotic vertebral compression fracture (OVCF) susceptibility . A total of 286 unrelated postmenopausal Korean women (57 with OVCFs, 55 with non‐OVCFs, and 174 healthy controls) were recruited and four SNPs from pre‐miRNA sequences miR‐146aC>G (rs2910164), miR‐149T>C (rs2292832), miR‐196a2T>C (rs11614913), and miR‐499A>G (rs3746444) were examined.…”
Section: Mirna Polymorphisms and Human Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Variants in miR‐146a, miR‐149, and miR‐196a2 were reported to associate with skeletal traits in multiple cohorts . Recent studies have further revealed several novel polymorphisms (let‐7g, miR‐140‐5p, miR‐149, miR‐3679, miR‐4274, miR‐433, miR‐499, and pri‐miR‐34b/c) that were significantly associated with skeletal traits . To date, 13 miR‐SNPs were found to be associated with skeletal traits and they are summarized in Table .…”
Section: Effects Of Mirna Polymorphisms On Skeletal Traitsmentioning
confidence: 99%
“…In bone, miR‐196a and miR‐146a were involved in osteoblast and osteoclast differentiation, whereas miR‐146a and miR‐149 were linked to rheumatoid arthritis (RA) and osteoarthritis (OA), respectively . The association of these SNPs with osteoporotic fracture was evaluated in a recent study composed of 286 postmenopausal Korean women (57 with osteoporotic vertebral compression fracture [OVCFs], 55 with non‐OVCFs, and 174 healthy controls) . It was reported that a combination of genotypes miR‐146aG/‐149T/‐196a2C/‐449G was associated with increased OVCF risk (OR = 35.01; 95% CI 1.919–638.6, p = 0.001).…”
Section: Mir‐snpsmentioning
confidence: 99%